Оптимізація біотехнологічних підходів у системі збереження генофонду свиней миргородської породи - Метлицька, О.І.; Щербак, О.В.; Ковтун, С.І.; Троцький, П.А.; Зюзюн, А.Б.; Осипчук, О.С. (Фактори експериментальної еволюції організмів, 2014)
Aims. Gene pool preservation endangered, indigenous pig breeds requires using methods modern biotechnology and genetic. Create a cryocollection Mirgorodska breed pigs viable oocytes and DNA bank for the development of scientific methods of maintenance and further improvement. Methods. In carrying out this work used biotechnology, cryobiological, morphological, molecular genetic methods. Results. As a result of working for long-term storage in the Bank Animal Genetic Resources of the Institute of Animal Breeding and Genetics laid full in vitro matured oocytes 25 sows Rysalka № 274/ 05 128, 19 oocytes Sojka № 314 and 53 oocytes Smorodina № 674 Mirgorodska breed pigs. For DNA studies the optimal treatment primary regimes biomaterial: ovarian tissue and immature oocyte cumulus complexes. Conclusion. Used complex biotechnology and molecular-genetic methods to form oocytebank pigs of Mirgorodska breed in Bank Animal Genetic Resources of the Institute of Animal Breeding and Genetics